Optimizing tower footing resistance and arcing horn length for improving lightning performance on 275 kv transmission lines - Abdul Rahman, Nur Afiqah; Ab. Kadir, Mohd Zainal Abidin; Abd. Wahab, Noor Izzri; Mailah, Nashiren Farzilah (Institute of Electrical and Electronics Engineers Inc., 2025)
High-voltage transmission lines at 275 kV are susceptible to lightning backflashover, with critical influencing factors including tower footing resistance (TFR), arcing horn configuration and lightning waveform characteristics. This paper present details analysis of the combined effects of TFR and arcing horn length under various of lightning waveshapes, examining how these variables interact to impact backflashover rate (BFR). Results indicate that optimizing TFR to lower values, particularly around 5Ω, mitigates BFR, especially in high GFD regions, by improving grounding efficacy. Furthermore, the relationship between arcing horn length and BFR is observed to be a non-linear, showing diminishing returns in BFR reduction beyond certain arcing horn lengths depending on the waveform type. A comparative waveform analysis reveals that shorter front times, as in the 0.25 / 100 μ s waveform, result in higher backflashover susceptibility than waveforms with longer rise and decay times, such as the 10 / 350 μ s waveform. These results suggest the critical role of waveform-specific mitigation strategies, as backflashover risk is heightened under certain lightning waveforms. This study supports adopting lower TFR values and optimized arcing horn configurations tailored to specific waveform characteristics and environmental exposure. Such adaptive approaches could lead to significant improvements in the resilience of transmission lines, reducing the frequency and severity of lightning-induced disruptions in high-voltage power systems, especially in regions with elevated lightning incidence.